Toward efficient bioremediation of methylmercury in sediment using merB overexpressed Escherichia coli. (1st February 2023) - Yang, Qingqing; Guo, Yingying; Xiang, Yuping; Chen, Lufeng; Liu, Guangliang; Liu, Yanwei; Shi, Jianbo; Hu, Ligang; Liang, Yong; Yin, Yongguang; Cai, Yong; Jiang, Guibin
Highlights: A recombinant strain E. coli DH5α J23106 overexpressing merB gene was constructed to degrade MeHg. DH5α J23106 degraded MeHg more than 81.6% in culture medium under anoxic/oxic conditions. DH5α J23106 degrade newly produced and intrinsic MeHg in actual Hg-contaminated sediment. Anoxic/oxic aging of MeHg in sediment decreased its degradation by DH5α J23106. Ammonium thiosulfate leaching, combined with DH5α J23106, enhanced the degradation of MeHg in sediment. Abstract: Sediment is the primary hotspot for microbial production of toxic and bio-accumulative methylmercury (MeHg). Common remediation strategies such as sediment dredging and capping can be too expensive and cannot degrade MeHg efficiently. Here, we constructed an Escherichia coli strain overexpressing merB gene (DH5α J23106) and assessed the effectiveness of this recombinant strain in degradation of MeHg in culture medium and sediment. DH5α J23106 can efficiently degrade MeHg (with initial concentration from 0.01 to 50 ng/mL) to more than 81.6% in a culture medium under anoxic and oxic conditions. Enriched isotope addition ( 199 HgCl2 ) revealed that this recombinant strain can degrade 78.6% of newly produced Me 199 Hg in actual sediment, however the biodegradation decreased to 36.3% for intrinsic MeHg. Degradation of spiked MeHg after aging in anoxic and oxic sediments further demonstrated DH5α J23106 can efficiently degrade newly produced MeHg and the degradation decreased with aging significantly, especially for oxic sediment. Eight sediments were further assessed for the biodegradation of aged MeHg by DH5α J23106 under oxic conditions, with degradation ratios ranging from 9.0% to 66.9%. When combined with (NH4 )2 S2 O3 leaching, the degradation of MeHg increased by 15.8–38.8% in on-site and off-site modes through enhanced MeHg bioavailability in some of these sediments. Thus, this recombinant strain DH5α J23106 can degrade MeHg efficiently and have the potential for remediating bioavailable MeHg in contaminated sediments. Graphical abstract: Image, graphical abstract